PENGUJIAN VIABILITAS SEMEN BEKU SAPI SIMMENTAL PASCA THAWING PADA SUHU DAN WAKTU YANG BERBEDA - , RUDAL JETTA BAYUSALAKSA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Livestock population increasement in Indonesian cattle industry require serious consideration. In effort to increase the livestock population, the utilization of frozen semen is considered as an option in artificial insemination. The major drawback in artificial insemination is the poor handling of frozen semen, and many other factor such as temperature prolonged post thawing time. The aim of this research is to understand the viability of simmentalâs frozen semen in variouse media tempreature and post thawing time. The thawing in research executed by picking 60 straws of Simmental Bull semen, 20 straws is thawed at 4- 8oC cold water, 20 more is thawed in tap water of 27 â 28oC temperature, and the last 20 straws is thawed in 35-37oC water, each thawing is executed for 20 second, and evaluated its spermatozoa post-thawing viability in every <1, 10, 30 minute, and 5 hour time range, under the microscope after applying eosin-negrosin staining. Obtained data will be analyzed with one way ANOVAs and t-test analysis tool. The research about Simmental bull frozen semen viability showed that there was significant differences of thawing results of cold, tap, and warm water thawing. The optimum result of thawing was done by warm water of 35-37oC temperature that only have <1 minute post thawing time. Keyword: Frozen semen, Simmental, thawing, post thawing